Fieldwork journals on Tonga's 2014 election: what's so funny about that? - Brown Pulu, T (Te Ara Poutama, AUT University, 2015)
This essay presents selected passages from the fieldwork journals of Teena Brown Pulu and Richard Pamatatau on Tonga’s 2014 election. Staged on November 27th, here was the second general election under an amended constitution intended to bring about a more democratic system of parliament and government. Woven together are interrelated factors which field researchers like us – academics who craft their written studies on encounters, observations, and conversations gathered from a specific people and place – experience and live through in day-to-day work. Highlighted in this paper are our reflections and recollections as Richard, a journalism academic, and Teena, an anthropologist, researching in the field while fielding a political climate of ordinary folks’ frustration. By this, Tongan people saw the nineteenth century class-system instituted in the 1875 constitution was fixed to the modified political structure introduced in 2010. Therefore, the thread interlacing our journal excerpts to an analysis of what is taking hold in Tongan political life is satire and wit, and how humour is manoeuvred to criticise and critique power and authority.